Le marquage prosodique du commentaire énonciatif dans la discrimination du sens des mots de discours: l'exemple de enfin - Petit, Mélanie (My University, 2009)
Our goal is to show the role of the prosody in the semantic and pragmatic characterisations of lexical uses, taking as illustration the discourse marker enfin and basing our researches on the prosodic analysis of 199 utterances of spontaneous French. We show that it is possible to improve the semantic description of this marker within linguistic semantics, in aid of prosodic configuration of utterances, notably distinguishing two levels of sense which are interpretation-type and use-type.